The Influence Of Conceptual Understanding Of Mathematics And Self Regulated Learning On Literacy Mathematical At Junior High School Students In The Regency Tangerang - Anandita Eka Febriana; Anwar Mutaqin; Novaliyosi (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
The purpose of this research is to investigate the impact of comprehending mathematics concepts and developing self regulated learning skills on the mathematical literacy of junior high school students in Tangerang district, all at the same time. The research methodology used is correlation-based, employing a quantitative approach. The research sample consists of 280 students, with one study group selected per school, specifically class VIII. The validity and reliability of the research statements were assessed using the Pearson correlation test, which demonstrated that all prepared statements were valid. Furthermore, after undergoing reliability testing, all the statements were deemed reliable. The classical assumption tests included normality testing using the one-sample Kolmogorov Smirnov test, a multicollinearity test, a heteroscedasticity test using Spearman correlation, and an autocorrelation test using Durbin-Watson. The research results show that the F-count value is greater than the F-table value with a correlation value of 0.429. It can be concluded that there is a substantial positive relationship between understanding mathematicss concepts and self-regulated learning on the mathematical literacy of junior high school students in Tangerang Regency.